What's new in target volume definition for radiologists in ICRU Report 71? How can the ICRU volume definitions be integrated in clinical practice? - Berthelsen, Anne Kiil (e-Med, 2007)
The optimal definition of the size, shape and location of gross tumour volume is one of the most important steps in the planning of radiation therapy, and necessitates a proper understanding of the procedure from both the oncologic radiologist and the radiation oncologist. This overview reports on the different terms and concepts that have been recommended in the ICRU Reports for this purpose; the latest Report 71 focuses on both previously given recommendations, and especially on electron beam therapy. This paper also highlights some of the problems that are encountered in the use of the International Commission on Radiation Units and Measurements (ICRU) recommendations in clinical practice, and at the interface between the radiation oncologist and the diagnostic oncologist.